Penerapan Model Pembelajaran Picture and Picture dalam Meningkatkan Motivasi dan Hasil Belajar IPA Terpadu SMP Negeri 3 Sitolu Ori Tahun Pembelajaran 2023/2024 - Rini Arian Susanti Harefa (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Low student motivation and learning outcomes in Integrated Science subjects remained a major problem in the learning process, particularly because learning activities tended to be teacher-centered and did not actively engage students. This study aimed to improve students’ motivation and learning outcomes through the implementation of the Picture and Picture learning model for seventh-grade students at SMP Negeri 3 Sitolu Ori in the 2023/2024 academic year. This study employed a Classroom Action Research (CAR) approach conducted in two cycles consisting of planning, action, observation, and reflection stages. Research data were collected through observation, learning motivation questionnaires, learning outcome tests, interviews, and documentation. The findings indicated that the implementation of the Picture and Picture learning model improved the quality of the learning process, student participation, learning motivation, and student learning outcomes. The percentage of students’ learning motivation increased from 70.04% in Cycle I to 95.6% in Cycle II. The average student learning outcomes also improved from 70.4 to 84.7, with learning mastery reaching 100%. The findings demonstrated that the use of visual images in Integrated Science learning created a more active, engaging, and meaningful learning environment, which positively influenced student participation and academic achievement.